Effect of Chain Length on Fatty Alcohol Sulfation using SO3-DMF - Sitinjak, Elvri Melliaty; Masmur, Indra; Tarigan, Dedi; Anggini, Cindy; Simbolon, Emma Juli Anamasta; Simatupang, Endang; Pane, Yulia Ratu; Simorangkir, Murniaty; Nurfajriani, Nurfajriani (Universitas Negeri Medan, 2023)
The fatty alcohols C8, C10, C16 and C18 were used as raw materials for the sulfation reaction using the SO3-DMF complex to study the ratio of carbon chains. The first step is to prepare the SO3-DMF complex, by reacting SO3 gas into DMF at a temperature of 0-4 0C with a reaction time of 3 hours, then sulfation is carried out at 100 0C for 5 hours on C8, C10, C16 and C18. Tests were carried out on the results of sulfation with an FT-IR Spectrophotometer. Surface tension, foam stability and yield calculations. From the sulfation results, the yield results were respectively 83%, 81%, 68% and 61% then the results from the surface tension analysis were 35.3, dyne/cm, 30.3 dyne/cm, 29.4 dyne/cm and 33.6 dyne/cm and foam stability analysis of 0.2 cm, 0.8 cm, 0.7 cm and 1 cm. Based on the surface tension reduction value, palmityl alcohol is the best raw material for making surfactants.